Channels for Financial and Non-financial Remittances from the Ghanaian Diaspora toward Development - Amanda Coffie (Revue Internationale de Politique de Développement)
This chapter deepens the discourse on diaspora and development in countries of origin. It proposes a shift from focusing narrowly on inflows of foreign currencies to also considering other forms of remittances such as goods, skills and ideas, which help maintain emotional bonds between family and communities across generations. Ghana acknowledges the diaspora’s beneficial role in development and has established gateways to facilitate the flow of resources. However, these formal gateways are skewed toward financial remittances, seen as the essential source for the State’s developmental agenda. With its varied composition and resources, the Ghanaian diaspora uses multiple channels to contribute toward their families and local community projects through individual contributions and resource pooling. Thus, the Ghanaian diaspora’s engagement reflects a participatory approach that has received limited State recognition but is appreciated and encouraged by recipients within Ghanaian communities. The chapter recommends government provision of secure channels for financial transfers while recognising cultural remittances and social connections as crucial for sustaining families, especially for reducing poverty and ensuring food security, which are specific and immediate concerns for communities.